High Turnover of Tissue Macrophages Contributes to Tuberculosis Reactivation in Simian Immunodeficiency Virus-Infected Rhesus Macaques. (8th February 2018) - Kuroda, Marcelo J; Sugimoto, Chie; Cai, Yanhui; Merino, Kristen M; Mehra, Smriti; Araínga, Mariluz; Roy, Chad J; Midkiff, Cecily C; Alvarez, Xavier; Didier, Elizabeth S; Kaushal, Deepak
Abstract : The rhesus macaque model of SIV and Mtb co-infection demonstrated that destruction of lung tissue macrophages promoted the transition from latent to reactivated Mtb. This was reflected by increased monocyte turnover that may be a predictive biomarker of Mtb reactivation. Abstract: Background: Tuberculosis (TB) and human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) profoundly affect the immune system and synergistically accelerate disease progression. It is believed that CD4 + T-cell depletion by HIV is the major cause of immunodeficiency and reactivation of latent TB. Previous studies demonstrated that blood monocyte turnover concurrent with tissue macrophage death from virus infection better predicted AIDS onset than CD4 + T-cell depletion in macaques infected with simian immunodeficiency virus (SIV). Methods: In this study, we describe the contribution of macrophages to the pathogenesis of Mycobacterium tuberculosis ( Mtb )/SIV coinfection in a rhesus macaque model using in vivo BrdU labeling, immunostaining, flow cytometry, and confocal microscopy. Results: We found that increased monocyte and macrophage turnover and levels of SIV-infected lung macrophages correlated with TB reactivation. All Mtb /SIV-coinfected monkeys exhibited declines in CD4 + T cells regardless of reactivation or latency outcomes, negating lower CD4 + T-cell levels as a primary cause of Mtb reactivation. Conclusions: Results suggest that SIV-related damage to macrophages contributes to Mtb reactivation during coinfection. This also supports strategies to target lung macrophages for the treatment of TB.